Meningitis patients with Angiostrongylus cantonensis may present without eosinophilia in the cerebrospinal fluid in northern Vietnam. - Tomoko Hiraoka; Ngo Chi Cuong; Sugihiro Hamaguchi; Mihoko Kikuchi; Shungo Katoh; Le Kim Anh; Nguyen Thi Hien Anh; Dang Duc Anh; Chris Smith; Haruhiko Maruyama; Lay-Myint Yoshida; Do Duy Cuong; et al. (Public Library of Science (PLoS), 2020)
Background Eosinophilic meningitis (EM) is a rare clinical syndrome caused by both infectious and noninfectious diseases. In tropical pacific countries, Angiostrongylus cantonensis is the most common cause. However, the EM definition varies in the literature, and its relation to parasitic meningitis (PM) remains unclear. Methodology/principal findings Adult and adolescent patients of 13 years old or above with suspected central nervous system (CNS) infections with abnormal CSF findings were prospectively enrolled at a tertiary referral hospital in Hanoi, Vietnam from June 2012 to May 2014. Patients with EM or suspected PM (EM/PM) were defined by the presence of either ≥10% eosinophils or an absolute eosinophil cell counts of ≥10/mm3 in the CSF or blood eosinophilia (>16% of WBCs) without CSF eosinophils. In total 679 patients were enrolled: 7 (1.03%) had ≥10% CSF eosinophilia, 20 (2.95%) had ≥10/mm3 CSF eosinophilia, and 7 (1.03%) had >16% blood eosinophilia. The patients with ≥10% CSF eosinophilia were significantly younger (p = 0.017), had a lower body temperature (p = 0.036) than patients with ≥10/mm3 CSF eosinophilia among whom bacterial pathogens were detected in 72.2% (13/18) of those who were tested by culture and/or PCR. In contrast, the characteristics of the patients with >16% blood eosinophilia resembled those of patients with ≥10% CSF eosinophilia. We further conducted serological tests and real-time PCR to identify A. cantonensis. Serology or real-time PCR was positive in 3 (42.8%) patients with ≥10% CSF eosinophilia and 6 (85.7%) patients with >16% blood eosinophilia without CSF eosinophils but none of patients with ≥10/mm3 CSF eosinophilia. Conclusions The etiology of PM in northern Vietnam is A. cantonensis. The eosinophil percentage is a more reliable predictor of parasitic EM than absolute eosinophil count in the CSF. Patients with PM may present with a high percentage of eosinophils in the peripheral blood but not in the CSF.